1994
DOI: 10.1073/pnas.91.8.3224
|View full text |Cite
|
Sign up to set email alerts
|

The insect tracheal system: a conduit for the systemic spread of Autographa californica M nuclear polyhedrosis virus.

Abstract: Baculoviruses establish systemic infections within susceptible insect hosts, even though host tissues are surrounded by basal lamlnae, extracellular matrices that exclude particles smaller than these viruses. Using a recombinant Autgrapha californwca M nuclear polyhedrosis virus containing a lacZ reporter gene under the control of a constitutive promoter, we followed the progression of infection in Tichoplusia ni larvae. We discovered that infection of the larval insect tracheal system (and not hemocytes, as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
165
0
6

Year Published

1997
1997
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 246 publications
(182 citation statements)
references
References 17 publications
9
165
0
6
Order By: Relevance
“…bud through the basolateral surface and initiate systemic spread of infection (Granados & Lawler, 1981). Infection may then spread quite rapidly throughout the insect by utilizing the tracheolar system of the insect (Engelhard et al, 1994). AcLP4 BV and PDV were able to cause lethal polyhedrosis when injected into T. ni larvae, but failed to cause infection when inoculation was by an oral route even with very high doses ; hence both midgut and systemic infection (by pass-through of nucleocapsids) were blocked.…”
Section: Discussionmentioning
confidence: 99%
“…bud through the basolateral surface and initiate systemic spread of infection (Granados & Lawler, 1981). Infection may then spread quite rapidly throughout the insect by utilizing the tracheolar system of the insect (Engelhard et al, 1994). AcLP4 BV and PDV were able to cause lethal polyhedrosis when injected into T. ni larvae, but failed to cause infection when inoculation was by an oral route even with very high doses ; hence both midgut and systemic infection (by pass-through of nucleocapsids) were blocked.…”
Section: Discussionmentioning
confidence: 99%
“…Several workers have shown the presence of virus particles in columnar cells of the midgut ( Kawanishi et al, 1972 andKeddie et al, 1989) early on infection. Other workers have shown, with the help of recombinant baculoviruses containing marker genes, that midgut epithelial cells support viral replication ( Volkman, 1997, Flipsen et al, 1995, Washburn et al, 1995, Knebel-Mörsdorf et al, 1996and Barret et al, 1998 and that the secondary infection was carried out by the insect tracheal system ( Engelhard et al, 1994 andBarret et al, 1998). We have shown previously in cell culture that AgNPV expression of very late genes (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has indicated that the insect tracheal system is responsible for the spread of the virus throughout the insect (Engelhard et al, 1994), but the passage of the virus through midgut epithelium is essential for the success of the infection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The BVs are produced in the nucleus of infected cells and are released to infect neighbouring cells within an infected insect. In the last phase of infection, the viruses are encapsulated in a protein envelope becoming ODVs, which are released to the environment and transmitted to other insects via oral infection 8 . Genes involved in the proliferation of NPVs are divided into three classes, early (immediateearly and delayed early), late, and very late genes, based on their expression time after virus infection.…”
Section: Introductionmentioning
confidence: 99%